Isolation and Identification of Cytotoxic and Antimalarial Constituents from Artemisia moorcroftiana. Issue 5 (1st February 2021) - Bhat, Khursheed A.; Naseer, Syed; Gani, Ifshana; Jameel, Salman; Amin, Henna; Bhat, Showkat Ahmad; Gupta, Ajai P.
Abstract: LC‐MS guided technique was applied for the detection and target separation of constituents of Artemisia moorcroftiana . Artemisinin together with fourteen other natural products viz; deoxyartemisinin, gorgonolide, 1‐β, 10‐α‐dihydroxy‐1, 10‐deoxygorgonolide, yangambin, epi‐yangambin, casticin, ergostanediene‐3‐ol, undecanol, artabsinolide diepoxide, campsterol, stigmasterol, artabsinolide A, artabsinolide C and 8, 11‐diethylpentadec‐14‐en‐2‐one were isolated from the aerial parts of Artemisia moorcroftiana Wall. The isolated molecules were subjected to MTT cytotoxicity screening against a panel of four different human cancer cell lines to check their cytotoxic potential. Casticin was found as the most potent cytotoxic isolate. In addition the phytochemical investigation has resulted into the isolation of known antimalarial constituents like artemisinin, casticin, gorgonolide and deoxygorgonolide which has confirmed the folklure claims associated with Artemisia moorcroftiana wherein it is reported to be used as an effective remedy for the treatment of malaria. Abstract : Artemisinin together with fourteen other natural products including a new molecule (8, 11‐diethylpentadec‐14‐en‐2‐one) were isolated from the aerial parts of Artemisia moorcroftiana Wall. The isolated constituents include known antimalarial/cytotoxic agents.